"Public Gardens, Halifax, NS, Thanksgiving Day, 1964, Arthur S. Pike and Hilda S. Pike" - Rorke Family (1964)
Arthur S. Pike and his second wife, Hilda Samways (Forward) Pike. Arthur S. Pike (?-ca. 1980) married Ernestine (Forward) Pike, daughter of Ernest Edward Forward and Tryphena (Butt) Forward, at Carbonear on 25 September 1913 and had 3 sons: Ernest, Arthur Jr. and Ralph. He later remarried to Ernestine's sister Hilda Samways Forward (1889-1982) on 5 June 1951, a little over a year after Ernestine's death. Arthur died around 1980. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.